2021
DOI: 10.3390/biom11081067
|View full text |Cite
|
Sign up to set email alerts
|

Synuclein Family Members Prevent Membrane Damage by Counteracting α-Synuclein Aggregation

Abstract: The 140 amino acid protein α-synuclein (αS) is an intrinsically disordered protein (IDP) with various roles and locations in healthy neurons that plays a key role in Parkinson’s disease (PD). Contact with biomembranes can lead to α-helical conformations, but can also act as s seeding event for aggregation and a predominant β-sheet conformation. In PD patients, αS is found to aggregate in various fibrillary structures, and the shift in aggregation and localization is associated with disease progression. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Alpha-synuclein modulates the release of neurotransmitters from presynaptic terminals by binding and clustering synaptic vesicles and chaperoning the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex assembly by binding to the protein synaptobrevin-2 (VAMP2) [ 28 , 29 ] whereas beta-synuclein and gamma-synuclein modulate the synaptic vesicular binding of alpha-synuclein and thus reduce the synaptic physiological activity of alpha-synuclein [ 30 , 31 ] ( Table 1 ). Moreover, in vitro and in vivo experiments have revealed that all three members of the synuclein family have chaperone activity [ 32 , 33 , 34 ].…”
Section: Synuclein Structure and Functionsmentioning
confidence: 99%
“…Alpha-synuclein modulates the release of neurotransmitters from presynaptic terminals by binding and clustering synaptic vesicles and chaperoning the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex assembly by binding to the protein synaptobrevin-2 (VAMP2) [ 28 , 29 ] whereas beta-synuclein and gamma-synuclein modulate the synaptic vesicular binding of alpha-synuclein and thus reduce the synaptic physiological activity of alpha-synuclein [ 30 , 31 ] ( Table 1 ). Moreover, in vitro and in vivo experiments have revealed that all three members of the synuclein family have chaperone activity [ 32 , 33 , 34 ].…”
Section: Synuclein Structure and Functionsmentioning
confidence: 99%